Just Noticeable and Objectionable Group Delays in Digital Hearing Aids - Agnew, Jeremy; Thornton, Jeffrey M. (Journal of the American Academy of Audiology, 2000)
Group delay in a digital signal processing (DSP) hearing aid may be perceived as an echo in the sound heard by a wearer listening to his or her own voice, due to a combination of unprocessed sound received at the ear through head and air pathways and delayed sound reaching the eardrum through the hearing aid. Depending on the amount, this delay may be audible or objectionable and can even result in auditory confusion. This study presents results from 18 subjects listening to their own voices through a DSP hearing aid with a variable group delay. The subjects varied the length of the delay and determined the amounts that were noticeable and objectionable as compared to the undelayed condition, while listening to their own amplified voices. Results indicated that a delay of 3 to 5 msec was noticeable to the listeners in 76 percent of the trials, and a delay of longer than 10 msec was objectionable 90 percent of the time.Abbreviations: DAF = delayed auditory feedback, DSP = digital signal processing, KEMAR = Knowles Electronics manikin for acoustic research
Keywords: Delay perception; digital signal processing; digital signal processing hearing aids; group delay